Edukasi Penyusunan Laporan Keuangan BUMdes Sumber Kamulyan Desa Wunut, Kabupaten Klaten - Trisulo Trisulo; Della Putri Wijaya; Fatika Rahmadhani; Rahmawati Rahmawati (Jurnal Nusantara Mengabdi, 2022)
Purpose: This study aimed to educate the Sumber Kamulyan Village Owned Enterprises (BUMDes) to produce standardized financial report outputs. Method: Training and Visiting (LAKU) method, with an individual approach was carried out. Data and information were analyzed descriptively and qualitatively to describe the problem through the depiction of events based on existing facts or evidence. Results: Sumber Kamulyan BUMDes got an understanding that the preparation of financial reports according to standards will be able to increase the accountability of BUMDes in the future. Conclusion: The knowledge of BUMDes managers in preparing financial reports according to standards increased.  The training and visitation system (LAKU) method which is commonly used in agricultural or livestock extension is quite effective in being applied to education in preparing financial reports to produce standardized financial report outputs.